Pandemics, Memes, and Sovereign Communication (Journal of Philosophy Culture and Political Science, 2020)
The article analyzes the relation between the pandemic diffusion of the Covid-19 and the infodemicsdetermined by the proliferation of memes and other digital means, trying to restore a strong sense ofidentity (the “sovereignist” virus). The pandemic is not simply the antithesis of globalization and neoliberalideology. In fact, it can be complementary to them, indicating a different path of developmentbetween technology, consumption and lifestyle. This is akin to what William Burroughs meant when heput forward his theory of language as a virus. The Word, Burroughs elaborated, infected the biologicalorganism of pre-alphabetic man, determining his expulsion from GOD (the “Garden of Delights”). Thehistory of human civilization is, therefore, read as a tremendous reversal of the relationship betweenbody and thought–in the sense that thought is read as an entity alien to the body that acts almost conspiratoriallywith respect to it.The author considers, that the blatant effect of the virus is not only to subvert the routines of expertsystems, but our perception of social reality taken for granted for too long.Key words: pandemic, memes, civilization, word, «sovereignist» virus.